HELQ upregulates PARP1 to drive platinum resistance and predict therapeutic response in ovarian cancer - Shuran Tan; Fang Zhu; Yi Li; Xinxin Wen; Siyu Yang; Zexi Liao; Xuerui Duan; Di Xiao; Yu Zhang (Translational Oncology)
POLQ-like helicase (HELQ), an evolutionarily conserved 3'-5′ DNA helicase, is markedly overexpressed in platinum-resistant ovarian cancer (OC), which is correlated with a poor prognosis. However, the mechanisms linking HELQ with resistance to platinum-based chemotherapy remain unkonwn. Our study presents both in vitro and in vivo evidence that elevated HELQ expression is linked to increased chemoresistance in OC models, with reduced HELQ levels enhancing their sensitivity to platinum agents. The expression of γH2AX, RPA1 and 53BP1 determined by immunofluorescence and western blot indicated that HELQ could promote platinum-induced DNA damage repair. HELQ was found to promote OC platinum resistance by regulating the expression of poly (ADP-ribose) polymerase 1(PARP1), which could be reversed by PARP1 downregulation. Furthermore, in vitro experiments showed that HELQ overexpression sensitizes OC cells to PARP inhibitors (PARPi). Immunohistochemical analysis indicates that diminished HELQ expression in tumor tissues correlates with disease progression in patients with first-line maintenance therapy with PARPi, whereby higher expression levels predict improved progression-free survival. Notably, we found a positive correlation between PARP1 and HELQ expression. In conclusion, HELQupregulats PARP1 to promote platinum resistance in OC and warrants consideration as an emerging biomarker for monitoring therapeutic responses to chemotherapy and PARPi treatment in ovarian cancer.